Clinical practice for migraine treatment and characteristics of medical facilities and physicians treating migraine: Insights from a retrospective cohort study using a Japanese claims database. - Tsubasa Takizawa; Takahiro Kitano; Kanae Togo; Reiko Yoshikawa; Masahiro Iijima (PLoS ONE)
The real-world treatment patterns at medical facilities and their physicians' specialties treating migraine have not been fully investigated in Japan. Therefore, a retrospective cohort study aimed to describe real-world clinical practice and treatment patterns in Japanese patients with migraine according to medical facilities and physicians' specialties. Anonymized claims data of patients with migraine was obtained from JMDC Inc (January 2018-June 2023). Patient characteristics and treatment pattern according to medical facilities and physicians' specialties treating migraine were evaluated. Of 231,156 patients with migraine (mean age [SD], 38.8 [11.8] years; females, 65.3%), 81.8% had the first prescription at clinics (CPs), 42.5% underwent imaging tests, 44.4% visited general internal medicine, and 25.9% consulted neurosurgery at initial diagnosis. Imaging tests were carried out at CPs with specialists (59.4%), hospitals (HPs) with specialists (59.1%), HPs (32.9%), and CPs (26.9%) without specialists. Overall, 95.6% received acute treatment while 21.8% received preventive treatment. At facilities with specialists compared to without specialists, triptans were more frequently prescribed (67.9% vs 44.9%) whereas acetaminophen and nonsteroidal anti-inflammatory drugs were less frequently prescribed (52.4% vs 69.2%). Preventive treatment use was higher at facilities with specialists (27.4%) than without specialists (15.7%) and increased annually regardless of the type of medical institution. In Japan, only half of patients with migraine visited facilities with specialists at their first diagnosis, and specialists are more likely use migraine-specific and preventive drugs than nonspecialists. Therefore, there is a need for awareness among migraine patients that they should consult specialists and for enhancement of medical collaboration between specialists and nonspecialists.